A Way To Use Banana Peel Waste as Pesticides and Insecticides: A Student-led project aimed at cultivating critical thinking skills - Siregar, Rabiyatul Adawiyah; Wulandari, Wulandari; Putri, Athifah; Rizky, Iffah; Maharani, Eehan (LAVOISIER: Chemistry Education Journal, 2024)
Plants that produce fruit are commonly found in Indonesia. This is because some Indonesians grow plants and utilize them as a business. To maintain good quality and quantity, the plants must be well cared for and protected from pests. Pests are organisms that often disturb or damage plants. Generally, pest control is more effective using chemical pesticides and insecticides, but for the environment and health, the use of chemical pesticides can have a negative impact. This occurs due to the prolonged use of chemical pesticides. With this, researchers used five different types of plants as the object of research, namely mango, durian, guava, avocado and orange. The results of using Barangan banana peel (Musa acuminata linn.) showed that Barangan banana peel can be used as a natural pesticide and has an effect on eliminating pests on plants. Therefore, the use of Barangan banana peel as a pesticide can be a solution for the community, and natural pesticides are also good for the environment and human body health.